Kegiatan Menggambar Bebas Menggunakan Crayon dalam Upaya Meningkatkan Kreativitas Anak Usia Dini - Veryawan Veryawan; Juliati Juliati; Rapita Aprilia (UIN Sultan Maulana Hasanuddin Banten, 2020)
This study aims to determine the mastery of the teacher's strategy in delivering free drawing learning materials using crayons that can increase children's creativity, provide interesting learning media in learning activities so that children's creativity can increase, provide opportunities for students to express all their ideas and ideas without any restrictions. in expressing colors in pictures and the teacher can understand and adjust learning outcomes with a standard level of achievement of children according to the stages of development. Classroom Action Research is a research process carried out by researchers through reflection with the aim of improving performance so that student learning outcomes increase. The planning model used is: Planning (planning), action (acting), observation (observing) and reflection (reflecting). The subjects in this improvement research were the children of group B TK Firza, totaling 15 children consisting of 6 boys and 9 girls. The field of development in this research is creativity with the activity is free drawing using crayons. The results showed the level of success in doing free drawing using crayons to improve children's creativity showed very good development and had reached the level of development in accordance with expectations, namely 80%. Thus, through free drawing activities using crayons can increase children's creativity. Keywords: drawing activities; creativity; early childhoodReferencesAnggia, A. R., & Nopriansyah, U. (2018). Mengembangkan Kreativitas Anak Melalui Permainan Warna Dengan Media Benang pada Anak Usia 5-6 Tahun di Raudhatul Athfal Perwanida I Bandar Lampung. http://ejournal.radenintan.ac.id/ index.php/al-athfaal/article/view/3789, 1(2), 1–20. Debeturu, B., & Wijayaningsih, E. L. (2019). Meningkatkan Kreativitas Anak Usia 5-6 Tahun melalui Media Magic Puffer Ball. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(1), 233. https://doi.org/10.31004/obsesi.v3i1.180Fathurohman, O. (2017). Hakikat Bermain Dan Permainan Anak Usia Dini Di Pendidikan Anak Usia Dini (PAUD). aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 27–36. Hidayat, F., & Imroatun, I. (2018). Keluarga Berencana Dan Pengasuhan Anak Usia Dini Di Indonesia Perspektif Psikologi. International Conference Proceeding Konsepsi dan Implementasi Pendidikan Islam Anak Usia Dini Book two, 164–171. Huliyah, M. (2016a). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Huliyah, M. (2016b). Pengembangan Daya Seni Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164. Isjoni. (2014). Model Pembelajaran Anak Usia Dini. ALFABETA. Ismayani, A. (2013). Fun Math With Children. In https://books.google.co.id/ books?id=0R5. Jumilah, Efastri, S. M., & Fadillah, S. (2018). Upaya Meningkatkan Kreativitas Anak melalui Permainan Finger Painting Usia 5-6 Tahun di TK Harapan Bunda Pekanbaru. PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2(1), 31–39. Larasati, L. D., Kurniah, N., & D., D. (2016). Peningkatan Kreativitas Dalam Kegiatan Mewarnai Dengan Menggunakan Metode Demonstrasi. Jurnal Ilmiah Potensia, 1(2), 62–66. Mulyani, N. (2019). Pengembangan Kreativitas Anak Usia Dini Melalui Bermain Gerak Dan Lagu Di TK Negeri Pembina Kabupaten Purbalingga. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 13–24. Nuryati, N., & Yuniawati, N. (2019). Peningkatan Kreativitas Pada Anak Usia Dini Kelas SD Awal Usia 6-8 Tahun Melalui Metode Praktikum Membatik. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 1–12. Pamadhi, H. (2012). Estetika Untuk Anak Usia Dini. Yogyakarta: Universitas Negeri Yogyakarta. Pamadhi, H., & Sukardi, E. (2013). Seni Keterampilan Anak. Jakarta: Universitas Terbuka. Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Santoso, F. S. (2020). Lingkungan Keluarga Sebagai Awal Pengembangan Kewirausahaan Islam. Nuansa Akademik Jurnal Pembangunan Masyarakat, 5(1). Setiani, & Nadjih, D. (2016). Pembentukan Karakter Anak Usia Dini Melalui Pendidikan Agama Islam Di TK ABA Kalibulus Rogobangsan Bimomartani Ngemplak Sleman. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 6(2`), 125–136. Tirtayati, N. P. E., Suarni, N. K., & Magta, M. (2013). Penerapan Metode Pemberian Tugas Untuk Meningkatkan Kreativitas Anak Melalui Kegiatan Menggambar Bebas. Jurnal Pendidikan Anak Usia Dini Undiksha, 2(1). Yulida, y, & Veryawan, V. (2018). Upaya Meningkatkan Kreativitas Seni Aank Melalui Kegiatan Teknik Kolase. Atfāluna: Journal of Islamic Early Childhood Education, 1(1), 19–23.